Novel Antidiabetic Molecules from the Medicinal Plants of Western Ghats of India, Identified Through Wide-Spectrum in Silico Analyses. Issue 3 (3rd July 2017) - James, Priyanka; Davis, Sangeetha P.; Ravisankar, V.; Nazeem, P. A.; Mathew, Deepu
ABSTRACT: The interaction of previously reported 656 phytocompound ligands with four well-characterized diabetic target proteins were studied in 20 plant species through in silico screening techniques. The binding energy, number of hydrogen bonds, and hydrogen binding residues with the receptor molecules were analyzed using the CDOCKER protocol of the software Discovery Studio 4.0. A total 23 molecules were found to have interaction with the four target proteins. Among these compounds, based on the ADME/toxicity profile, three promising drug candidates, namely, methyl gallate, ferulic acid, and anthranilic acid, were recommended as potential lead molecule for the treatment of type 2 diabetes mellitus.